Oltre le mura. Alla scoperta dell’Istituto Psichiatrico di Collemaggio (Itinera, 2019)
The research is the first scientific study about the ex psychiatric hospital in Collemaggio (AQ). It is related to some photographic plates regarding patients that were recovered in the asylum. Photography was an important instrument for the psychiatrists: they used it to study mental health through photos of patients’ bodies and faces. The photographic plates are compared to the experiments of Charcot, the innovations of Diamond and the psychiatric analysis of Lombroso.